1999
DOI: 10.1002/(sici)1521-3773(19990601)38:11<1583::aid-anie1583>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Phase-Transfer Catalysis

Abstract: Both in the laboratory and industrially, phase-transfer catalysis offers the potential to induce asymmetry into reactions with anionic intermediates. Equation (a) provides an example (conditions: a) 10 mol % phase-transfer catalyst, BnBr, CsOH⋅H O, PhMe, 15-24 h, -78°C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…Previous studies with acetic [36], mandelic [37], and tiglic [38] acids have indicated similar rotational restrictions, in those cases because the carboxylate ion fits in the bridging position of the open conformation of cinchonidine via a bidentate coordination [36]. All this is quite relevant to the performance of the cinchona alkaloids in catalysis, because their protonated quaternary quinuclidine nitrogen has been found to promote an array of asymmetric phase transfer reactions such as a-alkylation of carbonyl compounds, Michael additions, and epoxidation of enones [11,[39][40][41]. Protonation also appears to help in heterogeneous catalysis [42,43], and may be responsible for the medical properties of quinine [18].…”
Section: Solution Chemistrymentioning
confidence: 99%
“…Previous studies with acetic [36], mandelic [37], and tiglic [38] acids have indicated similar rotational restrictions, in those cases because the carboxylate ion fits in the bridging position of the open conformation of cinchonidine via a bidentate coordination [36]. All this is quite relevant to the performance of the cinchona alkaloids in catalysis, because their protonated quaternary quinuclidine nitrogen has been found to promote an array of asymmetric phase transfer reactions such as a-alkylation of carbonyl compounds, Michael additions, and epoxidation of enones [11,[39][40][41]. Protonation also appears to help in heterogeneous catalysis [42,43], and may be responsible for the medical properties of quinine [18].…”
Section: Solution Chemistrymentioning
confidence: 99%
“…[1] For example, the CH 2 group in CH 2 CHR can be replaced by 16-electron transition metal fragments [L n M] to give carbene complexes [L n M CHR], the CH group in HC CR can be replaced by 15-electron transition metal fragments [L n M] to give carbyne complexes [L n M CR], and a CH group in benzene can be replaced by 15-electron transition metal fragments to give metallabenzenes. [2] In principle, a carbon atom in benzyne could also be replaced by 14-electron transition metal fragments to give metallabenzynes.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Following the seminal work by O Donnell et al [2a] and Grabowski et al [2b] dramatic improvements in the asymmetric efficiency of PTC reactions were achieved by introducing (9-anthracenylmethyl)cinchonidinium (1 a, R allyl, benzyl, H) and other cinchoninium salts as catalysts for the enantioselective alkylation of N-(diphenylmethylene)glycine esters with electrophiles. [2c±e] Purely synthetic, chiral, C 2 -symmetrical ammonium salts were recently prepared and shown to be highly efficient in the same set of reactions.…”
mentioning
confidence: 99%
“…Many useful catalytic asymmetric phase-transfer alkylation reactions have been developed where the chiral counter-cation (Y*) ϩ is a quaternary ammonium salt (14,15). The synthesis of 6 is exemplary (Scheme 4) (16).…”
Section: Combination Of Chiral Carbon Nucleophiles With Carbon Electrmentioning
confidence: 99%